Healthcare workers in Saudi Arabia perceive stress differently according to gender but not in cortisol levels: an immunoassay study - Governo, Ricardo J. M.; Alyusuf, Danah A.; Gard, Paul R. (International Journal Of Community Medicine And Public Health, 2019)
Background: Working in the healthcare sector is generally regarded as stress inductive, which hampers performance, yet one demanding constant accuracy. This dichotomy has led to numerous investigations on the impact from perceived stress on hospital workers but focused primarily on employing psychological methods to determine perceived stress. This study sought to employ an arguably more objective measure of chronic stress on female healthcare professionals in Saudi Arabia, by assaying the concentration of hair cortisol (HCC) in parallel with stress questionnaires. Methods: Pharmacists, nurses and lab workers participated in providing hair samples. Cortisol levels were subsequently quantified using immunoassay methods. Investigations considered the variables of age, gender, and smoking, hair coloring or bleaching or working in shifts on both stress perception and HCC. Results: On average chronic stress was perceived comparably between the different healthcare professions and not differ significantly against the female control group. However, chronic stress differed significantly between genders within the healthcare profession. In contrast, HCC levels showed no direct relation to stress perception with respect to either gender or profession. HCC did, however, show steady decreases with respect to age, as an indirect measure of experience, that contrasted against the identical scores for stress perception. Finally, night shifts, smoking or hair colouring did not produce a significant change on HCC in the healthcare cohorts. Conclusions: Women in the healthcare profession perceive stress higher irrespective of profession compared to men. Also show a pattern of decreasing levels of cortisol with increasing age despite reporting similar stress perception against younger participants.